GAMBARAN KONDISI SANITASI SALURAN AIR LIMBAH DAN JAMBAN DI PASAR SEGIRI KOTA SAMARINDA - Wulan Fitri Anjaswati; Marjan Wahyuni; Reni Suhelmi (EnviroScienteae, 2023)
Traditional markets in Indonesia still have many problems both in terms of market management to market sanitation. Every activity in the market is mostly bound to produce wastewater, usually the most wastewater comes from meat and fish stalls because it uses a lot of water for washing, then wastewater also comes from MCK activities. The state of the market in samarinda city is still concerning in terms of sanitation, especially in terms of wastewater management and latrines. The purpose of this study is to find out an overview of the sanitary condition of wastewater drains and an overview of the sanitary condition of latrines in the Segiri Market, Samarinda City. The method used is to use descriptive qualitative. The results of the study based on the results of data collection carried out on wastewater channels in 15 los in Segiri Market, using observation sheets obtained the results of 8 qualified drainages and 7 unqualified drainages, based on the results of data collection carried out on latrines in 15 los in Segiri Market, using observation sheets obtained the results of 13 latrines qualified and 2 latrines were not qualified. The conclusion on the sewerage is that there are still many unqualified channels while for latrines it is quite good and many are qualified.